The Linguistic Policy of Certification of Foreign Language Competence at the Universidad de Antioquia: a Discourse Based Analysis - Restrepo Sepúlveda, Elsa Adriana (Íkala, Revista de Lenguaje y Cultura, 2012)
This article examines some discourses about the Linguistic Policy of the Certification of Foreign Language Competence (LP of CFLC) at the Universidad de Antioquia, with the aim of analyzing the findings, perceptions and positions of those who administer the policy regarding what it establishes and means. The article presents a methodological approximation based on a critical discourse analysis to tackle the subject. The analysis is done through some excerpts taken from the corpus of the study, which are constituted by: 1) Thirty semi-structured interviews applied to the board of professors that run the policy, postgraduate students, professionals and educators that have met the requirement of certification; and 2) the official documents that support the policy. The analysis makes it possible to identify the administrator's reflections on the LP of the CFLC. In addition, it unveils how through this type of discourse the certification requirement of foreign language competence has been naturalized and legitimized and how such a requirement serves as a mechanism for the compliance of the policy, acquiring a leading role. This requirement generates resistance against the linguistic policy, and not so much the assumed importance of the foreign language competence acquisition.